Assessing the Financial Soundness of Companies with Special Reference to the Indian Textile Sector: An Application of the Altman Z Score Model - Ahuja, Bhavna Ranjan; Singhal, Nitish (Indian Journal of Finance, 2014)
The Altman Z Score model is a useful tool to predict financial distress in business organizations operating across a wide variety of industries. Altman’s Z score, developed by Edward I. Altman, is a multiple discriminant analytical model used to determine bankruptcy of the companies by using commonly accepted cutoff criteria. In this research work, we provide a framework for the interpretation of the Z-Score model and apply it on selected companies operating in the Indian textile industry during the period from 2006 to 2011. The Indian textile industry is one of the largest sectors in the country in terms of output and employment. Given the high vulnerability of the Indian textile companies to the currently unstable western economy and volatile sales and earnings of textile manufacturers, there is an indispensable need to assess the financial position of the Indian textile sector.